2015
DOI: 10.1007/s00167-014-3489-0
|View full text |Cite
|
Sign up to set email alerts
|

Different intraoperative kinematics with comparable clinical outcomes of ultracongruent and posterior stabilized mobile-bearing total knee arthroplasty

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 39 publications
10
48
1
Order By: Relevance
“…Nonetheless, no notable differences were found for any type of adverse events between the two groups. Our finding is in accordance with previous studies reporting no increased incidence of adverse events with the e.motion-UC [38][39][40]. Our findings lead us to believe that the mobile-bearing UC prosthesis is a reasonably safe alternative to the mobile-bearing PS prosthesis when precise and meticulous surgical techniques are exercised.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Nonetheless, no notable differences were found for any type of adverse events between the two groups. Our finding is in accordance with previous studies reporting no increased incidence of adverse events with the e.motion-UC [38][39][40]. Our findings lead us to believe that the mobile-bearing UC prosthesis is a reasonably safe alternative to the mobile-bearing PS prosthesis when precise and meticulous surgical techniques are exercised.…”
Section: Discussionsupporting
confidence: 95%
“…This interesting finding is in agreement with previous studies reporting only a weak correlation between the postoperative maximum flexion and the clinical parameters for pain relief, joint function, and quality of life [41,42]. This study, along with previous midterm studies of TKAs performed with the e.motion-UC [38][39][40], indicates that the mobile-bearing UC prosthesis provides satisfactory functional outcomes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite the kinematic differences, studies have found equivalent clinical outcomes between PS TKA and UC inserts. 47,49,50,55,56 Some studies have also shown that UC inserts have comparable clinical outcomes to cruciate retaining TKA. 54,5759…”
Section: Ultracongruent Insertsmentioning
confidence: 99%
“…The most recent uses of Computer-Assisted-Surgery (CAS) in Total Knee Arthroplasty (TKA) provide the possibility to intra-operatively assess the functional behavior of the knee joint [7][8][9][10][11]. In particular, CAS is able to estimate range of motion and laxities associated with the patient and joint-specific surgical reconstruction.…”
Section: Introductionmentioning
confidence: 99%